2010
DOI: 10.1152/ajpcell.00168.2009
|View full text |Cite
|
Sign up to set email alerts
|

Iron supply determines apical/basolateral membrane distribution of intestinal iron transporters DMT1 and ferroportin 1

Abstract: Núñez MT, Tapia V, Rojas A, Aguirre P, Gómez F, Nualart F. Iron supply determines apical/basolateral membrane distribution of intestinal iron transporters DMT1 and ferroportin 1. Am J Physiol Cell Physiol 298: C477-C485, 2010. First published December 9, 2009; doi:10.1152/ajpcell.00168.2009.-Intestinal iron absorption comprises the coordinated activity of the influx transporter divalent metal transporter 1 (DMT1) and the efflux transporter ferroportin (FPN). In this work, we studied the movement of DMT1 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 50 publications
5
42
0
Order By: Relevance
“…Also yet to be well defined is the role of DMT1 (here shown with a ?) in possible basolateral uptake of iron noted in basolateral membrane vesicles [24] and recently supported [37]. Núñez et al also propose that Fpn can allow iron to exit back into the lumen of the GI tract (also shown here with a ?).…”
Section: The Tf Cycle: Iron Trafficking Into Erythroid Cells As Well supporting
confidence: 60%
See 3 more Smart Citations
“…Also yet to be well defined is the role of DMT1 (here shown with a ?) in possible basolateral uptake of iron noted in basolateral membrane vesicles [24] and recently supported [37]. Núñez et al also propose that Fpn can allow iron to exit back into the lumen of the GI tract (also shown here with a ?).…”
Section: The Tf Cycle: Iron Trafficking Into Erythroid Cells As Well supporting
confidence: 60%
“…Critical experiments are still needed to learn if these explanations for DMT1 movement are reliable. The findings that departure of DMT1 from the apical membrane correlates with decreased apical flux in Caco-2 cells and that antisense to DMT1 inhibits this flux [37] both support the mucosal block as an explanation, but participation of DMT1 in transcytosis is not excluded by such data. Iron exit from enterocytes depends on the transporter Fpn plus oxidation of Fe 2?…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The exact mechanisms by which iron is transported by DMT1 are obscure. We, and others (22,30), have observed that in intestinal epithelial cells with iron feeding DMT1 is internalized from the BBM into vesicles within the subapical cytosolic space. It is not known whether the internalization of DMT1 is required for iron transport and/or is part of the iron uptake regulatory mechanism, although transcytosis of vesicles derived from the apical BBM and vesicles derived from the basolateral surface has been described.…”
mentioning
confidence: 61%